Synthesis, characterization and ecotoxicological evaluation of hybrid graphene oxide-silver nanoparticles - Medeiros, Aline Maria Zigiotto de (2021)
The hybrid nanomaterial GO-AgNPs was synthesized using graphene oxide (GO) as substrate and stabilizer for the silver nanoparticles (AgNPs). This nanohybrid has promising technological applications due to its unique physicochemical properties. However, it is necessary to assess proactively the potential risks of these materials for human and environmental health. The aim of this thesis was an integrated ecotoxicological evaluation of the hybrid nanomaterial GO-AgNPs. It was realized in three main steps: i) Preparation and physic-chemical characterisation of the nanomaterial GO-AgNPs (e.g. composition, structure, morphology, size and chemistry of the surface); ii) Dispersion and colloidal stability monitoring (state of aggregation/agglomeration) of nanomaterials in the culture media of organisms-bioindicators and the influence of bio-coronas (environmental-corona and protein-corona); iii) ecotoxicity evaluation of GO-AgNPs, GO and AgNPs dispersions in vivo and in vitro assays of zebrafish model (Danio rerio). In the first chapter, a literature review was realised, and its scope summarises the synthesis, application and toxicological aspects of GO-AgNPs. An integrated study was reported in the second chapter and included the synthesis, characterisation, colloidal stability monitoring, and ecotoxicological assay in zebrafish embryos. GO-AgNPs were synthesised by the chemical reduction method of the silver salt in an aqueous dispersion of GO using sodium borohydride as a reducing agent. The characterisation techniques confirmed the formation of spherical AgNPS with an approximate diameter of 6 nm distributed onto GO sheets. The spontaneous coating formed by the natural organic matter, the eco-corona, positively influenced the stability of the nanomaterials and mitigated the toxicological response. The chorion also shows a protective function. Embryos without chorion exhibited higher rates of deformation and mortality compared to the control group. The median lethal dose (LC50-96h) was 1.5 mg L-1. In the third chapter, the effects of this nanohybrid on zebrafish liver cell line (ZFL) were evaluated. The protein-corona resulting from the interaction with the supplementation of the culture medium with fetal bovine serum (FBS) improved the colloidal stability of the nanomaterials. Mean inhibitory concentrations (IC50-24h) observed in viability assays (AB, MTT, NRU) ranged from 5.7 to 7.0 g mL-1. Furthermore, the assays with the embryo and with the liver cells showed the biocompatibility of GO even at high doses (100 mg L-1). Ingestion by embryos and internalisation by cells of this nanomaterial was also observed. The nanohybrid dissolution had a minor influence on the assessment, and most of the toxic response was due to the nanohybrid per se. Furthermore, the deleterious effects observed are distinct from the nanomaterials from their counterparts. Thus, the results reinforce the importance of proactive evaluation of this new nanomaterial to minimise the impacts on human and environmental health towards sustainability and responsible innovation